A Note on Causalities in Reaction Systems - Brijder, Robert; Ehrenfeucht, Andrzej; Rozenberg, Grzegorz (Electronic Communications of the EASST, 2010)
Reaction systems are a formal model of interactions between biochemical reactions. In this note we initiate an investigation of causalities in reaction systems which reflect the way that elements (entities) of a reaction system influence each other.Keywords: natural computing; biochemical interactions; reaction systems; causal relationships